Consensus on Quality Indicators for Pediatric Oncology Nursing Care in Mainland China: A Delphi Method and Analytic Hierarchy Process. (September 2022) - He, Mengxue; Lu, Hong; Shen, Nanping; Wu, Xinyi; Shen, Guomei; Zhou, Xuezhen; Shen, Min; Mo, Lin; Lily, Hsu
Background: Because routine nursing quality indicators are not suitable to evaluate pediatric oncology nursing care, this study aimed to identify a set of quality indicators for pediatric oncology nursing care in mainland China.Method: This prospective investigation utilized a modified Delphi technique and an analytic hierarchy process. A survey questionnaire was developed using a literature review and semi-structured interviews. Fifteen invited experts evaluated the importance of potential indicators through three rounds of Delphi survey by email in 2018. The importance weight of each indicator was identified through analytic hierarchy process.Results: In the Delphi survey, the average authoritative coefficient was 0.93–0.96 for each round of the inquiry. After three rounds of survey, 29 quality indicators were identified as important nursing outcomes for assessing the quality of pediatric oncology nursing care in mainland China. The importance rating mean score of indicators ranged between 4.67 and 5.00 on a 5-point scale, and the variation coefficient ranged between 0 and 0.19. Expert-assigned indicator importance weight varied between 0.0040 and 0.0870.Conclusion: This study identified an indicator system with 29 nursing-sensitive quality indicators that may represent potential indicator candidates for quality assessment of pediatric oncology nursing practice in mainland China.